Daya Kecambah Kabesak (Acacia Leucophloea) dan Asam Jawa (Tamarindus Indica) Menggunakan Variasi Bahan dan Waktu Perendaman - Arnold Christian Hendrik; Agus Maramba Meha (Savana Cendana, 2020)
In the cultivation of local forest plant species, knowledge of appropriate germination techniques is needed to obtain large quantities of seedlings with good quality seedlings. Kabesak (Acacia leucophloea) and tamarind (Tamarindus indica) were selected for this study because they are plants that have important economic and ecological benefits for local communities. The research objective was to determine the best use of variations of immersion materials and immersion time in increasing the germination of Kabesak and tamarind. The experimental design used in this study was a completely randomized design (CRD) with 2 factorials and 3 replications. The first treatment factor was immersion material with 3 treatments, namely immersion using hot water, MSG, and cow urine. The second factor was the immersion time with variations in the length of immersion for 6 hours, 12 hours and 24 hours. The results of the kabesak seed germination test showed that pretreatment was needed to soften the kabesak seed coat so that the imbibition process could run faster to spur the germination process. Soaking treatment with hot water produced the highest germination capacity compared to immersion treatment with other materials for A. leucophloea seeds. The best interaction for the immersion material and the length of soaking on the kabesak germination was the soaking treatment with hot water for 12 hours. For the tamarind germination test, it was found that the immersion material did not significantly affect the germination capacity of the seeds. The tamarind germination was significantly affected by the length of soaking, the best soaking was 6 hours.